2004
DOI: 10.1126/science.1102643
|View full text |Cite
|
Sign up to set email alerts
|

Realistic Species Losses Disproportionately Reduce Grassland Resistance to Biological Invaders

Abstract: Consequences of progressive biodiversity declines depend on the functional roles of individual species and the order in which species are lost. Most studies of the biodiversity-ecosystem functioning relation tackle only the first of these factors. We used observed variation in grassland diversity to design an experimental test of how realistic species losses affect invasion resistance. Because entire plant functional groups disappeared faster than expected by chance, resistance declined dramatically with progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
350
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(377 citation statements)
references
References 30 publications
20
350
1
6
Order By: Relevance
“…Within high-diversity assemblages, there should be fewer free resources available to an invading species than in low-diversity assemblages, which should make high-diversity assemblages more resistant to invasion. Our results, along with previous smallscale experimental work (Levine 2000;Naeem et al 2000;Dukes 2001;Kennedy et al 2002;Fargione et al 2003;Zavaleta and Hulvey 2004), support this prediction. Maron and Marler 2008) describing the relationship between resident native species diversity and the biomass of C. stoebe that established from seed experimentally added to plots differing in native species richness (C).…”
Section: Invasive Versus Native Target Speciessupporting
confidence: 80%
See 1 more Smart Citation
“…Within high-diversity assemblages, there should be fewer free resources available to an invading species than in low-diversity assemblages, which should make high-diversity assemblages more resistant to invasion. Our results, along with previous smallscale experimental work (Levine 2000;Naeem et al 2000;Dukes 2001;Kennedy et al 2002;Fargione et al 2003;Zavaleta and Hulvey 2004), support this prediction. Maron and Marler 2008) describing the relationship between resident native species diversity and the biomass of C. stoebe that established from seed experimentally added to plots differing in native species richness (C).…”
Section: Invasive Versus Native Target Speciessupporting
confidence: 80%
“…In our low-diversity assemblages, competition for light must have been relatively high as well, but it might have allowed the invasive alien species to survive and access soil resources untapped by native species. Previous experimental studies have shown that invasion by alien species can lead to an increase in productivity of lowdiversity assemblages (Zavaleta and Hulvey 2004;Maron and Marler 2008). This may be particularly the case when an alien plant species possesses traits that are uncommon or even absent among resident native species that enable it to exploit soil resources that remain untapped in lowdiversity assemblages (see also the discussion of C. stoebe below).…”
Section: Invasive Versus Native Target Speciesmentioning
confidence: 99%
“…Thus, if a Eurasian species is introduced to a new range, it is likely confronted with species it has coevolved with. On the other hand, the biota of North America is less disturbed by humans and richer than that of Europe and could thus offer more resistance to invaders (1,6,(17)(18)(19). We call this alternative to the imperialism dogma the resistance hypothesis.…”
mentioning
confidence: 94%
“…Changes in rainfall patterns and drought regimes can facilitate other types of ecosystem disturbances, including fire and biological invasion (Zavaleta and Hulvey, 2004). [WGII 14.4.2] Landward replacement of grassy freshwater marshes by more salt-tolerant mangroves, e.g., in the south-eastern Florida Everglades since the 1940s, has been attributed to the combined effects of sealevel rise and water management, resulting in lowered water tables (Ross et al, 2000).…”
Section: 625mentioning
confidence: 99%